Ar-Rahnu scheme as flexible micro financing mechanism for society: Case study on YAPEIM Ar-Rahnu in State of Perak - Fathil, Fathiah; Yaacob, Mazlah; Khalid, Nurul Khairiah; Fathil, Fauziah (TEXTROAD Publishing Corporation, 2017)
The implementation of ar-rahnuscheme which aims to assist the poor and enhance Islamic banking institution in Malaysia, since 1993 has proven to be able to provide immediate micro financing services to those with financial difficulties. Nevertheless, after two decades in operation, it is found that the involvement of members of Malaysian society in the scheme is still relatively low where the participants are mainly those of low income and the poor. The unique scheme which is not driven by profit-making and free of riba (usury) elements should be expanded to benefit all people and not confined to certain groups only. Hence, this study is conducted to identify the level of knowledge among general public about the ar-rahnu system and the level of acceptance among the masses of the scheme as a means to solve financial problems. It is hoped that the study which focuses on ar-rahnu institution of YaPEIM can be used as a guideline by relevant agencies or parties to ensure greater involvement of members of the society in the scheme, thus further augment the position of ar-rahnu institution in mainstream Islamic banking system in Malaysia.